2014
DOI: 10.1016/j.ijcard.2014.09.104
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and incidence of atrial fibrillation: A systematic review and meta-analysis

Abstract: Background: Whether physical activity increases or decreases the risk of atrial fibrillation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 26 publications
3
49
1
1
Order By: Relevance
“…124 In contrast, a meta-analysis suggested that more intensive physical activity was not associated with excess risk of AF (RR, 1.0; 95% CI, 0.82–1.22), but the heterogeneity statistic was significant. 176 …”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…124 In contrast, a meta-analysis suggested that more intensive physical activity was not associated with excess risk of AF (RR, 1.0; 95% CI, 0.82–1.22), but the heterogeneity statistic was significant. 176 …”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…Vigorous-intensity and high-endurance exercise has been reported to increase risk of atrial fibrillation particularly in athletes; however, 2 recent meta-analyses have failed to show an increased risk of atrial fibrillation for high intensity or high duration physical activity in the general population. 72,73 Moreover, regular engagement in low to moderate physical activity in the older adult appears to be associated with reduced risk of incident atrial fibrillation. 74,75 Physical activity is associated with reduced risk of incident stroke and reduced risk of mortality from stroke and is also protective of recurrent stroke in stroke survivors.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…To explore this effect, both physical activity and fitness should be examined, because they have different definitions and may be different physiological markers of cardiovascular diseases . Although several previous meta‐analyses have indicated the inconsistent effects of physical activity on AF among different populations and have demonstrated an inverse association of physical fitness with all‐cause mortality, coronary heart disease, and HF, little is known regarding the link between physical fitness and AF risk. Recently, epidemiological studies have explored the association between physical fitness and the risk of AF; however, they yielded conflicting findings.…”
Section: Introductionmentioning
confidence: 99%